Inovasi Edible Coating Buah Mangga Berbasis Kitosan Kulit Udang dengan Aditif Ekstrak Daun Asam Jawa sebagai Antimikroba - Pratama, Deska Rizki; Berutu, Aidha Sekar; Husin, Fahrizal; Panjaitan, Maychel Yohana; Taslim (Talenta Publisher (Universitas Sumatera Utara), 2025)
Edible coating is a thin layer that can be consumed which protects the surface of the fruit from environmental influences. This study evaluates the effectiveness of shrimp shell chitosan-based edible coating with tamarind leaf extract as an antimicrobial, along with glycerol and tween 80, in preserving mango quality during 15 days of storage. The variables evaluated were the concentration of tamarind leaf extract (0.5, 1.0, and 1.5%) and mango storage duration (0, 3, 6, 9, 12, and 15 days). While the amount of chitosan used was constant. The parameters measured included total microbial count, weight loss, fruit skin color, total soluble solids, titratable acidity, and vitamin C content. The results showed that the combination of shrimp shell chitosan and tamarind leaf extract as an antimicrobial significantly reduced the degradation of mango quality, with the 0.5% concentration of tamarind leaf extract being the most effective in maintaining quality and extending shelf life of mango until 15 days.